Compliance with and acceptability of two fortified balanced energy protein supplements among pregnant women in rural Nepal. Issue 2 (15th December 2021) - Lama, Tsering P.; Moore, Katie; Isanaka, Sheila; Jones, Leslie; Bedford, Juliet; de Pee, Saskia; Katz, Joanne; Khatry, Subarna K.; LeClerq, Steven C.; Tielsch, James M.
Abstract: Some evidence suggests that balanced energy protein (BEP) supplements taken during pregnancy and lactation can have positive effects on birth outcomes such as small‐for‐gestational age and birthweight, but more evidence is needed on the long‐term use and acceptability of such supplements. We conducted a mixed‐methods formative research study to assess and compare compliance with and acceptability of two BEP supplements, a lipid‐based peanut paste and a biscuit, to identify BEP supplements for subsequent inclusion in an efficacy trial. We conducted an 8‐week feeding trial of daily supplementation among two groups of 40 pregnant women each in rural Nepal. Compliance data were collected and supplements distributed at the weekly visits. Sensory properties of the supplements were assessed using a 7‐point Likert scale. In addition, in‐depth interviews with women ( n = 16), family members ( n = 6) and health workers ( n = 6) and focus group discussions (FGDs) ( n = 4) were conducted to explore themes related to general use and intention of future use of the supplement. Overall self‐reported compliance was high: medians of 91.1% in the lipid‐based peanut paste group and 96.4% in the biscuit group. Both supplements were rated highly on overall likability (median score 6/7) and sensory properties. Qualitative findings showed that sustained use of the supplements was attributed to expected health benefits, favourable sensory attributes, and family support. The FGDs suggested providing the option to choose between more than one type/flavour of supplements to improve compliance. Sharing was mostly evident in the first week with higher sharing reported in the biscuit group. Key messages: Both the lipid‐based peanut paste and the vanilla biscuit were well accepted by pregnant women in rural Nepal during an 8‐week home feeding trial. The compliance measurements showed high overall compliance in both supplement groups with the reasons being the perceived health benefits to the mother and baby, favourable sensory properties, enabling environment at home for product consumption (privacy and family support) and ease of product use. Before an efficacy trial of a nutritional food supplement, it is important to conduct a mixed‐methods feeding trial in the study population to understand the contextual factors that enable and prevent the use of supplements to inform ways to improve compliance with the supplements.